FUNDING IMPERATIVES IN NIGERIA EDUCATION SYSTEM: THE ROLE OF TERTIARY EDUCATION TRUST FUND (TETFUND) IN THE MANAGEMENT OF TERTIARY EDUCATION IN NIGERIA (Journal of Association of Educational Management and Policy Practitioners, 2024)
This paper examines educational funding in Nigeria as important, crucial and requiring immediate action. The paper points out different sources of funding education as well as the current state of educational funding in Nigeria. The paper presents the problem of funding education at tertiary level as a problem that affects the entire system of tertiary education as well as its programmes. The role of the government in funding education was captured by the paper with specific highlights on the role of TETFUND in funding Tertiary education in Nigerian tertiary institutions. The paper drew conclusions; stating that government alone cannot satisfactorily fund education in Nigeria; and that the private practitioners, parents/ guardian, international organizations as well as corporate institutions should step up the tides in  funding education in Nigeria; this is by replicating the role of TETFUND  and  the activities of the Non-Governmental Organization (NGOs) in funding education in Nigeria.